New Product Development for a Startup Company (WOODKA) - Prasojo, Faris; Indriani, Mia T. D. (Journal of Business and Management, 2015)
Abstract. WOODKA is a startup business established on September 2013 running in watch industry. WOODKA, as a new startup, needs to develop its line of product by expanding the product design and variety. Up until now, there is no specific design guideline that can be used to develop the next product varieties of WOODKA. Therefore, this research has the objective to explore WOODKA’s design strength according to customer and to find sets of important design attributes that is most preferred by costumer. The study was conducted using direct interview and mail survey which later analyzed with conjoint analysis. The direct interview was to find the most important attribute according to the provider and its previous customer input. The mail survey was later used to ask customer to give rank for the selected combinations which attributes are wood type (ARRO, KOVU, ORLA, NIEO), strap (pattern, leather, printed, plain), and watch’s shape (round, oval). The conjoint analysis was used to find the utilities and importance value of those attributes. The result of this study shows that the attribute that customer consider most in buying WOODKA’s product is the strap, which means that the concept of interchangeable strap WOODKA has really affect customer’s choice. Another result is that the most preferred attribute’s levels according to the utilities are leather strap, round-shaped watch, and ORLA wood type. Therefore, in the future development, WOODKA should try to focus more on developing those parts of its product. Keywords: Startup business, Customer preference, Conjoint analysis, New product development, Fashion accessories